Pemberdayaan Masyarakat melalui Budidaya Tanaman Hidroponik sebagai Alternatif dalam Menambah Pendapatan Masyarakat - Surindra, Bayu; Irmayanti, Elis; Afandi, Tjetjep Yusuf; Arifin, Zainal; Prastyaningtyas, Efa Wahyu; Lukiani, Eunike Rose Mita; Anggraini, Ari Saputri Novita; Dewi, Faradila Noer Kumala (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this activity is for the community to be able to optimally utilize the small land around the house by growing hydroponic plants. This activity was carried out in Sambiresik Village, Ngasem District, Kediri Regency, at Delta Sambiresik Permai 3 Housing. Hydroponic cultivation is carried out by providing plant nutrients using water instead of soil. In Sambiresik Permai Delta Housing 3, Sambiresik Village, the procedure for implementing community service includes location survey and observation, socialization, training and practice, mentoring, and monitoring. The advantages of this cultivation are that it can be done on a narrow land, faster growth and harvesting, and hydroponic plants can be sold at higher prices due to their superior nutritional value. As a result, the community's income will increase.